Analysis of stress intensity factor of a finite plate with centre crack containing different hole shapes. (2023) - Anoop Kumar, Amith; Arunkumar, S.; Arutselvan, C.K.; John, Jenuel
Abstract: The defects are usually formed in the components during the manufacturing process like for example, voids, microcracks or presence of secondary phase particles. These defects act as stress raisers and increase the severity of stress situation in the component. The structural integrity assessment of such components containing cracks are usually evaluated using fracture mechanics. In components containing flaws, subjected to linear elastic loads, the magnitude of the crack driving force or stress intensity factor (SIF), determines whether fracture occurs or not. In this work, the effect of different hole shapes (circular, square and elliptical) which are introduced in the vicinity of centre crack in a finite plate subjected to tensile load is investigated. The objective is to find out effectiveness of these holes in the arresting the crack growth when they are introduced along and perpendicular to the axis of the centre crack. This is accomplished through numerical simulation, where a two-dimensional model of finite plate with centre crack was created and validated against the analytical results. The holes are then introduced in a systematic manner to analyse its effect on the mode I SIF.